2019
DOI: 10.1247/csf.18033
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC00202 Promotes Tumor Progression by Sponging miR-3619-5p in Retinoblastoma

Abstract: Retinoblastoma (RB) is the most common intraocular malignancy in childhood, and the prognosis in the advanced RB is poor. It is urgent to find novel therapeutic targets. Long noncoding RNAs (lncRNAs) have critical functions in cancer progression, and lncRNA LINC00202 is found associated with poor prognosis in RB. However, the functions of LINC00202 in RB remain unclear. We employed qRT-PCR and immunoblot to detect the expression levels of mRNAs and proteins, respectively. Cell proliferation was determined by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…For instance, the low expression of miR-125a-5p in RB promoted cell growth [14]. The similar results about miR-3619-5p [6], miR-492 [15], and miR-758 [16] were also found in RB. MiR-655-3p has been reported to impact cell behaviors of tumor progression in ovarian cancer [17], non-small cell lung cancer [18].…”
supporting
confidence: 56%
See 1 more Smart Citation
“…For instance, the low expression of miR-125a-5p in RB promoted cell growth [14]. The similar results about miR-3619-5p [6], miR-492 [15], and miR-758 [16] were also found in RB. MiR-655-3p has been reported to impact cell behaviors of tumor progression in ovarian cancer [17], non-small cell lung cancer [18].…”
supporting
confidence: 56%
“…Many lncRNAs were reported to be dysregulated in RB and regulate biological processes in the tumor. For example, LINC00202 was highly expressed in RB, and its silencing retarded cell growth, metastasis in vitro [6]. THOR was up-regulated in RB, the depletion of THOR resulted in the decrease of cell growth, metastasis, and the increase of apoptosis [7].…”
mentioning
confidence: 99%
“…Compelling evidence indicates that miR-3619-5p could suppress β-catenin-mediated cancer growth and invasion in non-small cell lung cancer cells (34). In support of these findings, decreased miR-3619-5p expression has been detected in retinoblastoma cells, and transfection with miR-3619-5p mimic can improve the progression of retinoblastoma (35). In the present study, miR-3619-5p inhibitor reversed the effects of LINC00958 silencing on proliferation, invasion, migration and apoptosis of CRC cells.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies indicated that miR-3619-5p inhibits cell proliferation and migration in HCC [34]. miR-3619-5p is involved in LINC00202-mediated retinoblastoma progression through targeting the expression of an oncogene RIN1 [35]. miR-3619-5p has also been demonstrated to exert a tumor-suppressive role in several types of malignancies, including bladder cancer [36], lung cancer [37], prostate cancer [38], and cutaneous squamous cell carcinoma [39].…”
Section: Discussionmentioning
confidence: 99%